Transformation Of Indonesian Public Policy Law In The Digital Era: Utilization Of Artificial Intelligence In The State Financial System - Saputra, Muhammad Febriyan (Jurnal Hukum Malahayati, 2024)
Indonesia, as a developing country with dynamic economic growth, faces not only global challenges  caused by digital transformation but also stands at the forefront of exploring the utilization of Artificial  Intelligence (AI), including in governance and financial systems. The AI technology development opens  new opportunities in managing, optimizing, and overseeing the finances flow among government  entities. This research aims to analyze the Indonesian public policy law transformation in the digital era  related to the use of AI in the national financial system. It also seeks to analyze the development of  models, integration strategies, and regulatory efforts needed to achieve a balance between technological  efficiency and regional financial justice. The method used is normative research. The research results  indicate that there is currently no specific regulation governing AI in Indonesia. Conversely, the use of  AI technology has the potential to create several issues, such as analysis errors leading to  misinformation, copyright protection, and concerns related to human values. The developed models  should be oriented towards justice, integration strategies should ensure equal technology accessibility,  and regulatory efforts should focus on protecting people's rights and justice in fund allocation. Thus,  the AI technology implementations in the national financial system can provide optimal benefits and  simultaneously support inclusive and sustainable development throughout the regions. This research  specifically addresses regulations related to AI in Indonesia and contributes to legal developments in  Indonesia, particularly in the field of AI. This research novelty lies in the absence of similar studies  before, making it a new body of knowledge in the legal studies development.